Tissue-Specific Apocarotenoid Glycosylation Contributes to Carotenoid Homeostasis in Arabidopsis Leaves - Lätari, Kira (Plant Physiol, 2015)
Attaining defined steady-state carotenoid levels requires balancing of the rates governing their synthesis and metabolism. Phytoene formation mediated by phytoene synthase (PSY) is rate limiting in the biosynthesis of carotenoids, whereas carotenoid catabolism involves a multitude of nonenzymatic and enzymatic processes. We investigated carotenoid and apocarotenoid formation in Arabidopsis (Arabidopsis thaliana) in response to enhanced pathway flux upon PSY overexpression. This resulted in a dramatic accumulation of mainly β-carotene in roots and nongreen calli, whereas carotenoids remained unchanged in leaves. We show that, in chloroplasts, surplus PSY was partially soluble, localized in the stroma and, therefore, inactive, whereas the membrane-bound portion mediated a doubling of phytoene synthesis rates. Increased pathway flux was not compensated by enhanced generation of long-chain apocarotenals but resulted in higher levels of C(13) apocarotenoid glycosides (AGs). Using mutant lines deficient in carotenoid cleavage dioxygenases (CCDs), we identified CCD4 as being mainly responsible for the majority of AGs formed. Moreover, changed AG patterns in the carotene hydroxylase mutants lutein deficient1 (lut1) and lut5 exhibiting altered leaf carotenoids allowed us to define specific xanthophyll species as precursors for the apocarotenoid aglycons detected. In contrast to leaves, carotenoid hyperaccumulating roots contained higher levels of β-carotene-derived apocarotenals, whereas AGs were absent. These contrasting responses are associated with tissue-specific capacities to synthesize xanthophylls, which thus determine the modes of carotenoid accumulation and apocarotenoid formation.